PENGARUH BRAND EXPERIENCE, BRAND IMAGE-CONGRUENCE, BRAND AFFECT DAN BRANDTRUST TERHADAP REPURCHASE INTENTION PADA PRODUK FASHION BERRYBENKA SECARA ONLINE DI JAKARTA - WIBISONO SOEDIONO; KLEMENS WEDANAJI PRASASTYO; MARIA ADELINE (Media Bisnis, 2020)
The purpose of this study is to know how the influence of Brand Experience, Brand Image-Congruence, Brand Affect and Brand Trust to Repurchase Intention product online apparel Berrybenka at Jakarta.The research design used in descriptive research and causality research. The sampling used in this research is nonprobability sampling by purposive sampling methods and will require 107 respondents. The respondents must be using product online apparel Berrybenka. The method for analyzing data uses structural equation modeling (SEM), which uses the partial least square analysis program SmartPLS 3.0.The result showed that brand experience have an impact to brand affect. Brand image-congruence have an impact to brand affect. Brand experience have an impact to brand trust. Brand image-congruence have an impact to brand trust. Brand affect have an impact to brand trust. Brand experience have an impact to repurchase intention. Brand image-congruence have an impact to repurchase intention. Brand trust have an impact to repurchase intention.